Am I an engineer yet? Perceptions of engineering and identity among first year students. (3rd March 2020) - Lakin, Joni M.; Wittig, Ashley H.; Davis, Edward W.; Davis, Virginia A.
ABSTRACT: Development of a professional identity may contribute to persistence in an engineering major. Further, perceiving alignment of one's career values to engineering as well as believing that one is enacting engineering during coursework are expected to support identity formation. Using mixed methods approaches, we explored data provided by 186 undergraduate students responding to four open-ended questions at the end of an introduction to engineering course. Our results indicated alignment of perceptions of engineering and personal values, such as when students who emphasised the role of engineers as helping others tended to have altruistic professional goals. When considering identification with engineering, we found that definitions focused on the role of math and science as well as altruistic definitions were less likely to co-occur with a belief that students were already practicing engineering. Findings suggest certain definitions of engineering inhibit perceptions that the student is already enacting engineering and may affect identification.